Immunohistochemical Characterization of Endometrial Stromal Sarcomas - Marwah, Nisha; Kalyan, Monika; Bhargava, Shivani; Sunita Singh (Annals of Pathology and Laboratory Medicine, 2025)
Endometrial stromal sarcomas (ESS) are rare uterine mesenchymal tumors with overlapping histological and immunohistochemical features. High-grade ESS (HG-ESS) is typically characterized by high mitotic activity, marked pleomorphism, strong cyclin D1 expression, and negativity for hormone receptors. Accurate diagnosis is critical for appropriate treatment and prognosis. We report a case of a 75-year-old postmenopausal female presenting with abnormal uterine bleeding. Histopathological examination revealed a pleomorphic, highly cellular tumor with elevated mitotic activity (8–10/HPF). Immunohistochemistry showed strong positivity for vimentin, panCK, cyclin D1, ER, and PR. Beta-catenin staining was cytoplasmic and membranous, with no nuclear localization. SMA and MyoD1 were negative. Despite ER/PR positivity and absence of nuclear beta-catenin, the overall findings favored a diagnosis of high-grade endometrial stromal sarcoma. This case highlights the importance of integrating histomorphological features with a comprehensive IHC panel. Strong cyclin D1 expression, high mitotic index, and exclusion of other differential diagnoses supported the diagnosis of HG-ESS, despite conflicting ER/PR and beta-catenin findings.